The development of indigenous leadership in the church of the province of Southern Africa, with special reference to the diocese of St. Mark the evangelist - Kritzinger, J.J. (Johan Jakob) (University of Pretoria, 2013)
Thesis (PhD (Science of Regligion and Missiology))--University of Pretoria, 2006.